The effect of special training using some auxiliary tools In the development of special strength and achievement of throw by youth - Khamees Jaber, Khalid (International Journal of Psychosocial Rehabilitation, 2020)
As the use of these various auxiliary tools by projecting gradual resistances during the performance of the stages of this activity without prejudice to the motor paths required during the performance, especially for the stages of throwing and throwing, and this helps to increase their efficiency, and this problem summarizes the existence of limits and a level of this effectiveness in Iraq that cannot be overcome, and this What made the achievement not rise to the Arab, Asian, and Olympic levels, so the researcher resorted to using exercises and training aids to raise the level of physical abilities necessary in throwing the discus, which is the explosive and fast power, where the exercises included according to the performance of each stage and the study aimed to prepare special exercises using some Auxiliary training tools and to identify the impact of these exercises in developing the explosive and rapid power and the digital level of the research sample . As for the tests used in the research, they included tests of explosive and rapid strength and the digital level And the researcher conducted the main experiment for the period from Sunday, 8/3/2020, until Sunday , 5/3/2020, which included 24 units, 3 training units per week for a period of eight weeks , and the researcher concluded that the exercises used using rubber ropes, jumping boxes and other devices that were performed according to the effective performance had an impact on developing the explosive and rapid strength of the muscles of the legs, trunk and arms